PREPARATION AND STORAGE OF CUTLET FROM LOW- PRICED FISH - JOSEPH, JOSE; PERIGREEN, P A; THAMPURAN, NIRMALA (Fishery Technology, 2017)
Cutlets have been prepared from the minces oflizard fish ( Saw·ida tumbil), threadfin bream (Nemipterus japonicus), jew fish (Johnius dussumieri) and miscellaneous fish. The storage characteristics of cutlet (both raw and flash fried) at 4°C, -8°C and -20°C were studied. Cutlets prepared from the minced lizard fish showed the highest acceptability. Flash fried cutlets were found to be superior in quality compared to raw cutlets.The raw cutlet had storage life of 6 days, 11 weeks and 19 weeks at 4°C,-8°C and -20ocrespectively and flash fried cutlets had a shelf life of22 weeks at-20°C.